Komunikasi Pembangunan Desa Sesaot Dalam Menjaga Eksistensi Sebagai Desa Wisata Berkelanjutan - Septiyana Rizkika; Hartin Nur Khusnia; Dian Lestari Miharja (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2023)
ABSTRACT Sesaot Village is a tourist village in West Lombok Regency that was named the winner of the 2019 Indonesia Sustainable Tourism Awards in the environmental conservation category and received a Sustainable Tourism Village certificate by the Ministry of Tourism and Creative Economy in 2021. Its management carries the concept of Community Based Tourism, which involves the community in tourism development activities. With this concept, communication is needed as a tool or channel for conveying information so that tourism development ideas can be accepted by all parties. Therefore, the researcher wants to know how the development communication process of Sesaot Village in maintaining its existence as a sustainable tourism village. This research uses a qualitative method with a descriptive approach. The data collection techniques used were interviews, observation, and documentation. The results showed that there were tourism development innovations focused on managing the potential of the village into a Community Recreation Center. The development communication carried out is how an innovation can be accepted by the community, in the process the communication carried out is direct communication through socialization and deliberation activities, group communication collaboration between the village government and pokdarwis, and participatory development communication, namely participation in decision making, implementation, attracting benefits, and in evaluation. Through this communication process, development ideas can be accepted by the community and develop in revamping other village potentials into tourism packages. Keywords: Development Communication, Sustainable Tourism, Tourism Village. Kata kunci : Desa Wisata, Komunikasi Pembangunan, Pariwisata Berkelanjutan.